2017
DOI: 10.1371/journal.pone.0187720
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Zika virus replication and the development of Zika-specific antibodies after a mid-gestation viral challenge in guinea pigs

Abstract: Primary Zika virus (ZIKV) infections that occur during pregnancy can cause spontaneous abortion and profoundly disrupt fetal development. While the full range of developmental abnormalities associated with congenital Zika syndrome is not yet known, severe cases of the syndrome can present with microcephaly, extensive neurologic and ocular damage, and pronounced joint malformations. Animal models that accurately recapitulate congenital Zika syndrome are urgently needed for vaccine development and for the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
0
23
1
Order By: Relevance
“…Several other animal models have been used to study ZIKV but most are not focused on sexual transmission. These models include guinea pigs [109][110][111], hamsters [112], bats [113], chick embryos, piglets [114,115] and boars [116]. Porcine fetuses were shown to present mild to severe neuropathology upon ZIKV infection [114,115].…”
Section: Other Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other animal models have been used to study ZIKV but most are not focused on sexual transmission. These models include guinea pigs [109][110][111], hamsters [112], bats [113], chick embryos, piglets [114,115] and boars [116]. Porcine fetuses were shown to present mild to severe neuropathology upon ZIKV infection [114,115].…”
Section: Other Animal Modelsmentioning
confidence: 99%
“…The guinea pig models report conflicting results. One study with ZIKV challenge mid-gestation showed no evidence of infection [109]; however, Kumar et al show guinea pigs inoculated subcutaneously with PRVABC59 had viremia and presented signs such as fever, hunched posture and detectable viral RNA in the blood [110]. Deng et al showed that intranasally-infected guinea pigs have virus in the sera, saliva and tears [111].…”
Section: Other Animal Modelsmentioning
confidence: 99%
“…ZIKV H/PF/2013 (passage 4) was obtained from the European Virus Archive (001v-EVA1545) and cultured using previously established protocols [11]. ZIKV was passaged on Vero cells to generate working stocks of virus which were then concentrated by the ultracentrifugation of virus-containing media over a sucrose cushion, as described previously [12]. Multiple working ZIKV stocks were made from the same parent stock.…”
Section: Zikvmentioning
confidence: 99%
“…In addition to subcutaneous infection, other infection routes including intranasal infection and contact transmission of Zika virus could be demonstrated using the guinea pig model, highlighting its suitability to study transmission pathways [ 227 ]. However, not all clinical aspects can be reproduced, as circulating ZIKV strains seemed not to be pathogenic during the pregnancy of immunocompetent guinea pigs and did not interfere with offspring development [ 228 ]. Nevertheless, in contrast to other small animal models, the guinea pig model is physiologically and immunologically more similar to humans [ 229 ].…”
Section: In Vivo Modelsmentioning
confidence: 99%